Rancang Bangun Purwarupa Sistem Navigasi Tanpa Awak untuk Kapal - Budi Cahyo Suryo Putro; Adian Fatchur Rochim; Eko Didik Widianto (Jurnal Teknologi dan Sistem Komputer, 2016)
Indonesia is a maritime country with two of the three area consists of sea with a very favorable potential of the Indonesian economy. However. many thefts occur in marine fish Indonesia. Each year, the state must lose up to 11.8 trillion as a result of illegal fishing in the Arafura Sea. he Government has attempted to reduce losses due to illegal fishing by deploying surveillance vessels to conduct surveillance, but the ship still has limitations on deadlines related to logistics and fuel oil. Therefore, research must be done to develop a system of unmanned ship for patrol boats to patrol autonomously without the use of fuel oil. The system consists of hardware and software. The hardware consists of sensors such as GPS and compass as a navigational reference, Sonar sensor for obstacle avoidance, ATMega 2560 as a microcontroller and motor driver as the actuator. The software is built using C with Arduino IDE compatible with AVR microcontroller. The system will read the GPS coordinates and compass direction in order to run unmanned. The system is also equipped with a transmitter to control the system manually. The results show the system is able to move the ship to navigate automatically. The system able to read the GPS coordinates and the reading direction of the compass well. The system also able to avoid obstacles that are in front of the system. The system is also able to be manually controlled and can transmit serial data to identify the condition of the system.